Evaluation of the impact of school canteen programs on schooling and combating school wastage of students in rural schools in Morocco - Fatima Azdagaz; Mariem Liouaeddine; Omar Zirari (Development Studies Research)
Promoting education in rural areas and combating school dropout remain critical challenges for Morocco's education sector. In this context, this study aims to evaluate the impact of the school canteen program on student enrolment and efforts to mitigate school dropout in rural schools. The analysis is based on data from a national social support survey conducted by the National Human Development Observatory (ONDH) in 2018, involving a representative sample of 3,039 rural and urban households. Employing a micro-econometric approach, specifically the propensity score matching (PSM) method, the findings reveal a significant effect of school canteens in reducing repetition rates among rural students. However, the study did not find conclusive evidence of a positive impact on enrolment rates for these students. Additionally, the evaluation explores the integration of this program, assesses its targeting strategy, and highlights critical factors for achieving a high-performing education sector that emphasizes both accessibility and quality.